Emotional Catharsis To Overcome Depression In Symptoms Of Mental Disorders With Mediators Journaling Therapy In Early Adulthood - Rindang Wahjuningtijas (Journal Of Social Science (JoSS), 2023)
The National Adolescent Mental Health Survey (I-NAMSHAS) 2023 shows mental health problems are most worrisome because 1 in 3 adolescents experience mental health, 1 in 20 have symptoms of mental disorders in the past 12 months and 15.5 million (34.9 percent) adolescents experience moderate mental problems, one of which is an indication of depression. Depression is a mood disorder, where a person's prolonged emotional condition colors the process of feeling thinking and behaving a person. Journaling or journaling is an action taken to express ideas, thoughts, and even emotions into the form of writing, images, whose benefits can be attributed to relieve mental disorders. Excessive stress often disturbs the physical and mental individual, before it happens you should immediately do prevention, one of which is to do journaling therapy. Early adulthood is a period that is considered a critical period after escaping from adolescence, which occurs in the 20s to 30s which he considers critical because this stage is the initial stage of career and family formation. The conclusion of this discussion is the process of using catharsis methods to reduce mental health disorders in someone in early adulthood (aged 20-30 years), after doing emotional catharsis through journaling techniques each respondent feels better because there is a channeling of his emotions and finally feels better, journaling techniques are the right emotional catharsis media in reducing or relieving symptoms of mental disorders.